Sublethal and intergenerational effects of fipronil on Binodoxys communis larvae based on transcriptome sequencing - Du, Lingen; Zhao, Likang; Zhu, Xiangzhen; Wang, Li; Zhang, Kaixin; Li, Dongyang; Ji, Jichao; Niu, Lin; Luo, Junyu; Cui, Jinjie; Gao, Xueke (Frontiers in Environmental Science, 2022)
Fipronil is widely used in the agricultural world as an efficient phenylpyrazole insecticide to control pests. Binodoxys communis is a key parasitic natural enemy of major homopteran pests and can successfully control the population of pests such as cotton aphids. It has not yet been studied what effects would sublethal doses of fipronil have on Binodoxys communis larvae. Here, this study evaluated the effect of fipronil on Binodoxys communis larvae and analyze the transcriptome results. The results showed that LC10 (1.19 mg/L) and LC25 (1.73 mg/L) had significant negative effects on the survival rate and parasitism rate of F0 generation. Moreover, exposure to high concentrations (LC25) of fipronil still had obvious passive effect on the F1 generation of Binodoxys communis. These results indicated that sublethal doses of fipronil have malignant effects on the biological functions of parasitoids and their offspring. The results of transcriptome analysis showed that differentially expressed genes (DEGs) of Binodoxys communis after LC10 treatment are mainly related to immunity and detoxification. LC25 treatment instead resulted in changes in the expression of genes related to nutrition, energy and metabolism reactions. Seven of the identified DEGs were selected for real-time fluorescence quantitative PCR analysis. To the best of our knowledge, this is the first report to evaluate the sublethal, intergenerational, and transcriptomic side effects of fipronil on larvae of parasitic natural pest enemies. Our findings provide data to accurately assess the risk of fipronil usage on Binodoxys communis larvae, and provide important theoretical support for the comprehensive prevention and control of natural enemies and pesticides.